Dialogic Social Impact Analysis of Companies and Organizations (DSIACO): A pioneer model for evaluating social impact of companies and organizations - Mar Joanpere; Ana Burgues-Freitas; Cristina Pulido; Adriana Aubert; Elisabeth Torras-Gómez; Maria Vieites; Marta Soler-Gallart; Ramon Flecha (PLoS ONE, 2025)
Scientific literature has clarified that companies’ social impact is crucial in improving society by optimising their performance and relationship with their stakeholders, creating long-term value. Companies are increasingly interested in assessing their social impact. For instance, applying regulatory compliance increases investors’ confidence, reputation, and image. It reduces risks and costs and improves decision-making, resilience, and talent retention. The concept of social impact and the scientific basis for evaluating and enhancing it have also been clarified and officially published by international organisations (besides the scientific literature). However, there is a lack of scientific literature on how to analyse companies’ social impact based on scientific evidence of social impact. Building upon the latest contributions of the ALLINTERACT research project, funded by the European scientific programme Horizon 2020, we have focused on analysing the social impact of companies and institutions. Our work is based on the communicative methodology of research, which pioneered the development and proposal of the criteria of social impact and co-creation. In this regard, a twofold goal is addressed in this study. On the one hand, a systematic literature review has been conducted to identify existing models of social impact evaluation for companies and organisations based on scientific evidence of social impact. On the other hand, the Dialogic Social Impact Analysis of Companies and Organisations model for assessing social impact tailored for companies and institutions is presented, which has been previously developed as a result of scientific research about social impact evaluation in different fields. The results of the systematic literature review extracted from the screening of 387 articles and analysis of 70 of those articles revealed the absence of any model developed enough to assess companies’ social impact based on scientific evidence of social impact. Existing models make critical errors like confusing social impact with transference. Hence, the DSIACO model presented in this article addresses this critical gap and drives scientific advancements in this area.